Sequência didática para o ensino da termodinâmica - Lima, Joslaine de (2016)
The purpose of this study was to develop and to implement a didactic sequence for thermodynamics teaching with the use of ICT. The development of this material was mainly based on the guidance of Marco Antônio Moreira (2012) concerning Potentially Significant Teaching Units. It was implemented in a 2nd grade class at a public High School, in the city of Campo Mourão PR. Videos and simulators were used in order to propose a contextualization to lead students to discuss the issues, besides raising other issues in order to identify the students' background knowledge regarding the target content.